Altered production of penicillin-binding protein 2a can affect phenotypic expression of methicillin resistance in Staphylococcus aureus. - Hackbarth, C J (1994)
Altered production of penicillin-binding protein 2a (PBP 2a) may affect the phenotypic expression of resistance in methicillin-resistant Staphylococcus aureus (MRSA). COL, an MRSA strain that constitutively produces PBP 2a, was transformed with a recombinant plasmid containing the two beta-lactamase regulatory genes, blaI and blaR1, with either the beta-lactamase gene, blaZ, or a truncated blaZ. Both of the transformed MRSA strains now produced an inducible PBP 2a, and the MICs of nafcillin, methicillin, and imipenem for these strains were similar to those for the parental strain. A mutation in blaR1 that resulted in the complete repression of PBP 2a production altered the phenotypic expression of methicillin resistance in that strain, as evidenced by efficiency-of-plating experiments. Rather than being homogeneously resistant like COL, the blaR1 mutant strain now appeared to have a small resistant subpopulation. Gene products that regulate PBP 2a production may contribute to the organism's expression of methicillin resistance, but additional chromosomally located factors are required.